2003
DOI: 10.1111/1471-3802.00008
|View full text |Cite
|
Sign up to set email alerts
|

Setting or mixed ability? Teachers’ views of the organisation of pupils for learning

Abstract: This paper examines how staff in schools formulate decisions about pupil organisation. A small sample of primary and secondary schools from across Scotland was involved in the study.In 1996 Her Majesty's Inspectors published a report entitled Achievement for All (SOEID, 1996) which, it was envisaged, would form the basis of school evaluations into the effectiveness of classroom organisation. This report, and in particular the six principles on which it suggested effective organisational arrangements should res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…However, increased university participation in the UK, USA and Europe has meant this is a growing issue, as illustrated by this subject coming up in all workshops. There is scant research on the benefits or otherwise of undergraduate mixed ability classes, but research on compulsory education (Reid et al 1981, Ireson et al 2002, Smith and Sutherland 2003, Boaler 2008 has illustrated the advantages in terms of learning, confidence and motivation of mixed ability classes, although the picture on academic achievement is not so clear for maths (Ireson et al 2002).…”
Section: Dealing With Mixed-ability Classes and Lack Of Confidencementioning
confidence: 99%
“…However, increased university participation in the UK, USA and Europe has meant this is a growing issue, as illustrated by this subject coming up in all workshops. There is scant research on the benefits or otherwise of undergraduate mixed ability classes, but research on compulsory education (Reid et al 1981, Ireson et al 2002, Smith and Sutherland 2003, Boaler 2008 has illustrated the advantages in terms of learning, confidence and motivation of mixed ability classes, although the picture on academic achievement is not so clear for maths (Ireson et al 2002).…”
Section: Dealing With Mixed-ability Classes and Lack Of Confidencementioning
confidence: 99%
“…Pupils interviewed were acutely aware of the importance and amount of testing to which they were subjected and this caused a lot of anger and resentment. The suggestion by some of the pupils interviewed that behaviour could also be a criteria for set allocation and indeed for movement between sets is borne out by other research (Smith & Sutherland, 2003; Ireson et al, 2002). The realisation that such factors were involved seemed to indicate to some pupils that allocation to sets was not about merit but based on inaccurate and subjective opinions by staff.…”
Section: Discussionmentioning
confidence: 89%
“…Thus it may be that in top sets the pressure becomes greater because the expectations of teachers, parents and of the pupils themselves become greater on the allocation of the pupil to the top set. In a study into staff attitudes towards setting (Smith and Sutherland, 2003) staff reported that set classes were more purposeful and focused. Two key questions emerge here: why is it that set classes are more purposeful and focused and what is taking place in mixed ability arrangements that make them seem less so?…”
Section: Discussionmentioning
confidence: 99%
“…This aspect can be seen in a positive way: grouping students in small groups by ability allows for differentiated, concentrated learning to occur in a focused, safe environment. Smith and Sutherland (2003) identified in their study that perceived advantages of cross-class ability grouping (setting) could be seen, such as:…”
Section: Ability Groupingmentioning
confidence: 99%
“…Despite a lack of research and evidence to favour setting as the most effective organisational method, many schools in Scotland have changed their organisational procedures (Smith & Sutherland, 2003). There is, therefore, a contradiction apparent with policy makers in that 'setting' continues to be implemented, although research for this type of grouping is limited.…”
Section: Ability Groupingmentioning
confidence: 99%